Potential of Oyster Mushroon (Pleurotus ostreatus) and Gluten in the Production of Artificial Meat with High Fiber Content - Wardani, Nela Agustin Kusuma; Widjanarko, Simon Bambang (Jurnal Teknologi Pertanian, 2013)
The purpose of this study was to obtain a method of making artificial meat with the use of oyster mushrooms and gluten. This experiment was also studied the effect of different proportion of oyster mushroom flour and gluten on the physicochemical and organoleptic properties of an artificial meat. Teoritical evaluation of protein nutritional value was also studied. Randomized Block Design (RBD) was used in this experiment with flour proportion of oyster mushroom : gluten ratio as single factor. Each experiment was repeated 4 times. Percentage increase of oyster mushrooms addition on wheat gluten dough are J1 = 0% (w/w); J2 = 10% (w/w); J3 = 20% (w/w); J4 = 30% (w/w). Based on experimental results, the best treatment Â of physicochemical parameter was proportion of oyster mushroom flour and gluten (30:70) which had moisture content of 73.16%, protein content 16.21%, 84.02% WHC, texture 21.81 N, pH 6.72, and color (L = 40.84; a + = 18.00, b + = 22.53). On the other hand, the best treatment of organoleptic properties obtained from the proportion of oyster mushroom flour and gluten (10:90) with level of preferences were 3.65 (neutral) for taste, 4.55 (somewhat like) for texture and color, and 4.05 (neutral) for aroma. For the best treatment (proportion of oyster mushroom flour and gluten (30:70)) of SEM (Scanning Electron Microscopy) showed that there were many holes in large quantities and the size of hole was large. Product with organoleptic parameter (proportion of oyster mushroom flour and gluten (10:90)) had small fewer holes (porous). In addition, the texture surface looked rougher than control. The quality of digestibility, biological value and NPU of the best treatment in series were 94.50%, 40.15% and 37.94% for physicochemical parameters, and 95.54%, 33.92%, and 32.41 % for organoleptic parameters.Keywords: Oyster mushrooms, gluten, artificial meat